Sanctions Mechanism for Notary Who Break the Code of Ethics - Yuli Sambira (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Notary is a public official who is appointed by the Government and entrusted with the authority to make a written deed in the form of an authentic deed. Not only do notaries have the task of making authentic deeds in certain fields, but in almost every field of civil law where the Notary is authorized to make them. In carrying out his position, a notary is demanded to be more sensitive, honest, fair and transparent in order to ensure the implementation of the goals and obligations of all parties directly involved in making authentic deeds. In carrying out his / her duties, a notary must adhere to the code of ethics of the notary's office, because without it his professional dignity will be lost and he will not gain the trust of the public. The Notary Code of Ethics is a self-control for Notaries in carrying out their duties. The scope of the Notary Code of Ethics applies to all Notaries or those who hold and carry out a Notary position. The Indonesian Notary Association as the parent association for Notaries, has a very important role in enforcing the implementation of the Professional Code of Ethics for Notaries. In upholding the Code of Ethics, there must be harmony between the Notary concerned, professional colleagues, the community and professional organizations, in this case the Indonesian Notary Association, through the Honorary Council which has the main task of supervising the implementation of the Code of Ethics.